THE ROLE OF MIRZO ULUGBEK'S SCIENTIFIC ARCHITECTURE IN WORLD SCIENCE - Moʻydinov Muhammadali (European Science Publishing, 2023)
The article describes the personality of our great-grandfather, the great scholar, the enlightened ruler, Mirza Ulugbek, and his contribution to world science. A number of changes and updates to his tenure have been analyzed.
Keywords: Timorese, Central Asia, Tajikistan, Ziji Jadidiy Ko'ragoni, Historical Arba Ulus.